53-x+8=4x-27+1

Simple and best practice solution for 53-x+8=4x-27+1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 53-x+8=4x-27+1 equation:


Simplifying
53 + -1x + 8 = 4x + -27 + 1

Reorder the terms:
53 + 8 + -1x = 4x + -27 + 1

Combine like terms: 53 + 8 = 61
61 + -1x = 4x + -27 + 1

Reorder the terms:
61 + -1x = -27 + 1 + 4x

Combine like terms: -27 + 1 = -26
61 + -1x = -26 + 4x

Solving
61 + -1x = -26 + 4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-4x' to each side of the equation.
61 + -1x + -4x = -26 + 4x + -4x

Combine like terms: -1x + -4x = -5x
61 + -5x = -26 + 4x + -4x

Combine like terms: 4x + -4x = 0
61 + -5x = -26 + 0
61 + -5x = -26

Add '-61' to each side of the equation.
61 + -61 + -5x = -26 + -61

Combine like terms: 61 + -61 = 0
0 + -5x = -26 + -61
-5x = -26 + -61

Combine like terms: -26 + -61 = -87
-5x = -87

Divide each side by '-5'.
x = 17.4

Simplifying
x = 17.4

See similar equations:

| (2w+3)2+2x=42 | | 3(7-2k)=57 | | -8+4m^2-5m^2= | | 7x+3-2x+9=47 | | z-8.4=4 | | (x+(2+i))(x+(2-i))=0 | | -0.2(212-h)=8.6 | | 5x-10=39 | | 5.25b=22.75 | | -5x-2=-x-7 | | 3(x+1)+3(x+3)= | | 14x-(4x-5)=45 | | 7x-26=2x+54 | | -7(5k-5)=-210 | | 25-3u=24 | | 95=5X+2X+7 | | 2=10-1.6d | | 95=5X+2X+7 | | 95=5X+2X+6 | | 95=5X+2X+6 | | 5x-3(x-5)=-8+4x+17 | | 95=5X+2X+6 | | 6u-40=3(u+4)-4 | | 6u-40=3(u+4)-4 | | 8(10+3+5v)-2v= | | 5y-35x=-35 | | 2+4g=5+1g | | 5u+5=-26u | | 3x-30=3x-9 | | (3r+8)=(r-4) | | n+6=9*5 | | 3x-30+6-15=3x-9 |

Equations solver categories